Program Pengungkapan Sukarela Terhadap Tax Ratio dan Kepatuhan Sukarela Wajib Pajak - Mahwiyah Mahwiyah; Mochamad Aditia Rachmawan; Yuliandi Akbar; Sunarto Sunarto; Suripto Suripto (CV. ULIL ALBAB CORP, 2024)
The Voluntary Disclosure Program (PPS) allows taxpayers to voluntarily disclose unreported tax obligations for PPH payments based on their assets. The research method used is qualitative, with data collected from several Primary Tax Service Offices in Tangerang by distributing questionnaires with questions related to voluntary disclosure, the tax ratio, and taxpayer compliance to a number of respondents. The results show that voluntary disclosure has a positive and significant effect on the tax ratio, as indicated by the analysis results. Similarly, voluntary disclosure also has a positive and significant impact on taxpayer compliance. The panel data regression analysis reveals that voluntary disclosure influences both the tax ratio and taxpayer compliance, with the analysis results supporting this conclusion. Overall, the voluntary disclosure program positively and significantly affects both the tax ratio and taxpayer compliance.